Healthy Village Toward Gebrak (Joint Movement of PKK and Cadres) Caring for The Nutrition of Pregnant Women Based on Local Wisdom in Kusamba Village, Bali - Fitria, Fitria; Dewi, A. A. Santi; Saraswati, A. A. Sagung Ratu; Noviani, Ni Wayan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aimed to increase public knowledge, awareness, and concern regarding the importance of fulfilling the nutritional needs of pregnant women through educational and participatory approaches. The program was implemented through counselling sessions, training on making fish floss, and mentoring of posyandu cadres. The target participants were 25 PKK members and 25 posyandu cadres from Kusamba Village, Klungkung, Bali Province. The implementation adopted a Participatory Action Research (PAR) approach, which aimed to empower the community by providing direct experience in service activities. Considering the conditions of existing partners—namely the PKK and posyandu cadres—new ideas were developed to diversify supplementary feeding (PMT) programs using local wisdom in Kusamba Village to improve maternal nutrition. The results showed: (1) a 98% increase in community knowledge regarding the nutritional needs of pregnant women and chronic energy deficiency (CED); (2) a 100% increase in knowledge about animal-based foods and the nutritional content of skipjack tuna; (3) the successful creation of skipjack tuna floss products (100% success rate); (4) the ability to operate floss-making and oil spinner machines with a 100% success rate; and (5) a 96% improvement in self-capacity, financial management, and product marketing. These outcomes demonstrate that community-based nutrition initiatives for pregnant women can serve as an effective strategy to support sustainable maternal and child health programs grounded in local wisdom and community participation.